THE USE OF SCHOOLOGY MEDIA IN ENGLISH LEARNING EVALUATION PROCESS - Setyawan, Aris (JIPIS, 2021)
This study aims to find out the effectiveness of Schoology media in English Learning evaluation process. Evaluation is one of activity learning process that should be done by teacher, in this case, teachers to be able to do the evaluation process to know how far their students had understood about the learning process. However, there are some difficulties for teachers to do evaluation in learning process. It is very important for the teachers to use interesting media to help them in evaluation process. This study aims to find out the effectiveness of Schoology in English learning. The study was conducted in one of Senior High Schools in Tangerang Banten named SMAIT Asy-Syukriyyah. Qualitative method was employed for this study. Based on the result of this research, the researcher found that Schoology media is effective to help the teacher to do evaluation in his learning. Keywords: Evaluation Process, Learning Media, Schoology